Being a hermeneutic of the gospel : hermeneutical and epistemological foundations for a missional ecclesiology - Sheridan, Timothy Michael (Stellenbosch : Stellenbosch University, 2012)
Thesis (DTh)--Stellenbosch University, 2012.